2008
DOI: 10.1902/jop.2008.070667
|View full text |Cite
|
Sign up to set email alerts
|

Local Peptidergic Innervation of Gingiva in Smoking and Non‐Smoking Periodontitis Patients

Abstract: Background: The present study aimed to investigate the local peptidergic innervation of diseased and healthy periodontia in smokers and non‐smokers. Methods: Fifteen smokers and 12 non‐smokers, all with localized chronic periodontitis, participated in the study. Periodontally diseased and healthy tooth sites were selected in smokers (groups 1 and 2, respectively) and non‐smokers (groups 3 and 4, respectively). Local peptidergic innervation was assessed by the concentrations of two neuropeptides, substance P (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…It has been shown in many studies that the severity of gingivitis and periodontitis among smokers is higher than that among non-smokers (28,29). It has been determined that compared to non-smokers, smokers place less importance on oral health care; thus, plaque accumulation is more common among smokers, and they are more prone to periodontal disease (30).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in many studies that the severity of gingivitis and periodontitis among smokers is higher than that among non-smokers (28,29). It has been determined that compared to non-smokers, smokers place less importance on oral health care; thus, plaque accumulation is more common among smokers, and they are more prone to periodontal disease (30).…”
Section: Discussionmentioning
confidence: 99%
“…Substance P is also detected in gingival tissues and gingival crevicular fluid, which is correlated with the degree of periodontal inflammation; it has been shown that a reduction in inflammation as a result of effective periodontal treatment is associated with a reduction in the level of SP in gingival crevicular fluid (14,15). Furthermore, Norevall et al (16) reported that the expression of SP was increased after orthodontic tooth movement in rat periodontal ligament specimens, and Sakalliog˘lu et al (17) found increased SP concentrations in periodontitis sites compared with healthy sites in the mouths of smokers. These observations suggest that SP is involved in remodeling the periodontal ligament and alveolar bone in periodontitis or during orthodontic tooth movement.…”
mentioning
confidence: 99%
“…(16) reported that the expression of SP was increased after orthodontic tooth movement in rat periodontal ligament specimens, and Sakallioğlu et al. (17) found increased SP concentrations in periodontitis sites compared with healthy sites in the mouths of smokers. These observations suggest that SP is involved in remodeling the periodontal ligament and alveolar bone in periodontitis or during orthodontic tooth movement.…”
mentioning
confidence: 99%
“…Sensory fibres of the maxillary and mandibular divisions of trigeminal nerve innervate periodontal tissues, and this sensory innervation is closely associated with blood vessels (Lundy & Linden, ). The immunomodulatory role of certain neuropeptides in periodontal disease has become reasonably acceptable after the identification of several neuropeptides in the gingival crevicular fluid (GCF) (Luthman et al, ; Luthman, Johansson, Ahlström, & Kvint, ; Sakallıoğlu et al, ) and gingiva (Bartold, Kylstra, & Lawson, ). During the neurogenic inflammatory state vasodilatation, plasma extravasation and immune cell recruitment are modulated by sensory neuropeptides, and, peptide‐containing nerve fibres close to immune cells and their functional neuropeptide receptors on the immune cells have been identified in periodontium (Lundy & Linden, ; Luthman et al, ; Sakallıoğlu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The immunomodulatory role of certain neuropeptides in periodontal disease has become reasonably acceptable after the identification of several neuropeptides in the gingival crevicular fluid (GCF) (Luthman et al, ; Luthman, Johansson, Ahlström, & Kvint, ; Sakallıoğlu et al, ) and gingiva (Bartold, Kylstra, & Lawson, ). During the neurogenic inflammatory state vasodilatation, plasma extravasation and immune cell recruitment are modulated by sensory neuropeptides, and, peptide‐containing nerve fibres close to immune cells and their functional neuropeptide receptors on the immune cells have been identified in periodontium (Lundy & Linden, ; Luthman et al, ; Sakallıoğlu et al, ). Therefore, the neurogenic response in inflammatory reactions, called as the neurogenic inflammation, is also speculated to be involved in periodontal disease (Lundy & Linden, ; Luthman et al, ; Sakallıoğlu et al, ).…”
Section: Introductionmentioning
confidence: 99%